Bamboo-like amorphous carbon nanotubes clad in ultrathin nickel oxide nanosheets for lithium-ion battery electrodes with long cycle life. (April 2015) - Xu, Xin; Tan, Hui; Xi, Kai; Ding, Shujiang; Yu, Demei; Cheng, Shaodong; Yang, Guang; Peng, Xiaoyu; Fakeeh, Amir; Kumar, R. Vasant
Abstract: In this work, we report the synthesis of one-dimensional (1-D) hierarchical NiO nanosheets covering bamboo-like amorphous CNT composites (NiO@CNT) via a facile and a low-cost solution route based on sulfonated polymeric nanotubes (PNTs) used simultaneously as both, a template, and a source of nano-structured carbon derived by a low-temperature thermal carbonization treatment. The electrochemical performance of the NiO@CNT composite electrode indicate that this novel hybrid nanostructure is potentially capable of delivering excellent reversible capacity when used as an anode material in a lithium-ion battery (LIB). A large discharge capacity of 1034 mAh g −1 is delivered by the NiO@CNT composite even after 300 cycles at a relatively high current density of 800 mA g −1, with an average coulombic efficiency of 98.1%. A significant achievement in the reversible capacity of the NiO@CNT composite is attributed to the outstanding nanostructure resulting in synergistic effects of the hollow amorphous CNT backbone and ultrathin NiO nanosheets. Furthermore, the generic solution method to fabricate 1-D metal oxides@amorphous CNT nanostructures, developed in this work, is expected to have a wide range of applications in improving the properties of transition metal oxides.